Inter-Sector Collaboration in Implementation Poverty Alleviation Program Through Corporate Social Responsibility in Indonesia - Ashari Salam; Muh Ridwan B (Universitas Warmadewa, 2024)
To effectively align corporate social responsibility (CSR) with poverty reduction agendas, companies need to be more inclusive and collaborative with other actors. Cross-sector partnerships in CSR implementation have emerged as a new approach and practice, as promoted by public administration scholars. Key actors in partnerships may come from government, civil society represented by non-governmental organizations (NGOs), and corporations. However, designing successful and effective partnerships that are relevant to cross-sector dynamics and political contexts has proven to be a challenge, especially in developing countries and new democracies, such as Indonesia. This paper provides the main characteristics of effective cross-sector partnerships derived from examining three case studies in Indonesia and Tanzania. Both represent cross-sector partnerships with varying scope and depth. In this paper, one can observe and extract the main characteristics of effective partnerships based on the three case studies, each with its described model. In particular, the characteristics used to assess the effectiveness of the model include ownership, alignment and synchronization, accountability, reduced dependency, resource sharing, along with representation and legitimacy.